Development of a weighted leanness measurement method in modular construction companies - Saba Shams Bidhendi; Steven Goh; Andrew Wandel (Journal of Industrial Engineering International, 2019)
This paper outlines the development of an improved approach to the use of lean tools and techniques to improve the performance of manufacturing enterprises. Several research studies attempt to measure the overall leanness score of the manufacturing process; however, they failed to consider the interdependent relationships between lean performance metrics and considered all performance measures to be equally important during analysis. This paper proposes the weighted leanness assessment methodology to further extend the most recent developed leanness assessment model. The developed methodology in this research provides an integrated leanness score of the production process which considers the interrelationships between~different performance metrics due to competing for business and operational strategies. The fuzzy-based analytic network process approach is used to measure and allocate relative importance weightings to each performance metric. The result from the proposed methodology in this research provides a more accurate overall leanness score by prioritising different performance measures according to the manufacturer's needs. A case study was conducted to illustrate the effectiveness and validity of the proposed model and methodologies.
Keywords: 650; Lean manufacturing; Lean strategies; Leanness assessment tools; Fuzzy logic; Analytical network process